CDR 2018
DOI: 10.20517/cdr.2017.03
|View full text |Cite
|
Sign up to set email alerts
|

Identification and targeting of CD22ΔE12 as a molecular RNAi target to overcome drug resistance in high-risk B-lineage leukemias and lymphomas

Abstract: AimCD22ΔE12 as an oncogenic driver lesion in aggressive and drug-resistant B-precursor acute lymphoblastic leukemia (BPL) cells. The purpose of the present study was to identify the CD22ΔE12-specific signature transcriptome in human BPL cells and evaluate the clinical potential of a nanoscale formulation of CD22ΔE12-siRNA as an RNAi therapeutic against drug-resistant BPL. CD22ΔE12-siRNA nanoparticles significantly improved the event-free survival (EFS) outcome of NOD/SCID (NS) mice challenged with human BPL xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…RNAi has become a promising therapeutic approach for cancer and its success can be observed at various stages of clinical trials in different malignancies [31][32][33]. In ALL, various targets have been successfully silenced by RNAi, such as Polo-like kinase 1 (Plk1), CD22ΔE12, CSF1R, JAK1 and FLT3 [34][35][36], all of which highlights the versatility of using RNAi for ALL therapy. In this study, we have shown the feasibility of siRNA-mediated STAT5A silencing in ALL cell lines SUP-B15 and RS4;11 as well as ALL patient cells from different donors, using 2 lipid modified PEIs.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi has become a promising therapeutic approach for cancer and its success can be observed at various stages of clinical trials in different malignancies [31][32][33]. In ALL, various targets have been successfully silenced by RNAi, such as Polo-like kinase 1 (Plk1), CD22ΔE12, CSF1R, JAK1 and FLT3 [34][35][36], all of which highlights the versatility of using RNAi for ALL therapy. In this study, we have shown the feasibility of siRNA-mediated STAT5A silencing in ALL cell lines SUP-B15 and RS4;11 as well as ALL patient cells from different donors, using 2 lipid modified PEIs.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published working database, including data on primary leukemia cells from 201 adult patients with B-ALL (GSE13159), 119 pediatric patients with B-ALL (GSE11877 and GSE13351) and 97 infants with B-ALL (GSE68720), as well as 74 normal/non-leukemic control bone marrow samples (GSE13159), was built with previously archived datasets from the NCBI repository and used in our comparative gene expression analyses, as previously described in detail [20] . We also used a working database derived from archived datasets including data on primary leukemia cells from 542 adult patients with AML (GSE13159), and 279 pediatric patients with AML (GSE19577, GSE17855) along with the 74 normal/non-leukemic control bone marrow samples (GSE13159) in our comparative gene expression analyses, as described [20] . Probeset level normalization procedures were used as previously reported [20] .…”
Section: Statistical Methods For Gene Chip Normalization For All and ...mentioning
confidence: 99%
“…We also used a working database derived from archived datasets including data on primary leukemia cells from 542 adult patients with AML (GSE13159), and 279 pediatric patients with AML (GSE19577, GSE17855) along with the 74 normal/non-leukemic control bone marrow samples (GSE13159) in our comparative gene expression analyses, as described [20] . Probeset level normalization procedures were used as previously reported [20] .…”
Section: Statistical Methods For Gene Chip Normalization For All and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…They describe a novel approach to reverse resistance by the use of siRNA, which suppresses the survival pathway in which RAS plays a role. Uckun and Qazi [18] also used siRNA (encapsulated in nanoparticles) to downregulate the CD22∆ E12 in drug-resistant B-precursor ALL. Unfortunately siRNA application is still limited to model systems, although carriers such as nanoparticles are being investigated to solve this problem.…”
Section: What Is Special In the First Issue?mentioning
confidence: 99%